Autophagy-lysosome pathway in insulin & glucagon homeostasis - Wu, Yi; Wang, Hui; Xu, Huoyan (Frontiers in Endocrinology, 2025)
Lysosome, a highly dynamic organelle, is an important nutrient sensing center. They utilize different ion channels and transporters to complete the mission in degradation, trafficking, nutrient sensing and integration of various metabolic pathways to maintain cellular homeostasis. Glucose homeostasis relies on tightly regulated insulin secretion by pancreatic β cells, and their dysfunction is a hallmark of type 2 diabetes. Glucagon also plays an important role in hyperglycemia in diabetic patients. Currently, lysosome has been recognized as a nutrient hub to regulate the homeostasis of insulin and other hormones. In this review, we will discuss recent advances in understanding lysosome-mediated autophagy and lysosomal proteins involved in maintaining insulin and glucagon homeostasis, as well as their contributions to the etiology of diabetes.